Mining the global diversity for bioenergy traits of barley straw: genomewide association study under varying plant water status. Issue 8 (30th March 2017) - Naz, Ali A.; Reinert, Stephan; Bostanci, Cihan; Seperi, Bahare; Leon, Jens; Böttger, Christian; Südekum, Karl‐Heinz; Frei, Michael
Abstract: Cereal straws constitute a considerable source of biomass that can be used for bioenergy applications. Its composition is crucial for the energy value in biological or thermochemical conversion processes. Therefore, this study aimed at (i) exploring the global diversity in the composition of barley ( Hordeum vulgare L.) straw; (ii) testing the effect of drought on straw composition; (iii) correlating compositional traits with energy value; and (iv) identifying loci associated with straw composition through genomewide association study (GWAS). A population of 179 barley accessions was grown in control and drought conditions, and straw was analyzed for thioglycolic acid lignin (TGAL), total phenolics (TP), carbon, crude protein (CP), C/N ratio, and ash. Substantial variability was observed in all traits. Moreover, drought treatment affected all traits leading to significant decreases in carbon, CP, ash, TGAL and TP concentrations, and a significant increase in C/N ratio. In vitro incubations in rumen fluid were used to estimate the energy value in biological energy conversion, while calorimetry was used to estimate the energy yield in thermochemical energy conversion. Thioglycolic acid lignin was singled out as the most influential trait determining energy value, as it was negatively correlated with the digestibility of organic matter and metabolizable energy in in vitro incubations, but positively correlated with gross energy measured by calorimetry. The GWAS yielded four loci significantly associated with TGAL irrespective of plant water status, which explained between 22.5% and 38.7% of the phenotypic variation. In addition, three loci significantly affected the response of TGAL to plant water status, and explained between 11.2% and 16.6% of the phenotypic variation. These loci contained plausible candidate genes that could be associated with lignin biosynthesis based on their annotations. In conclusion, this study illustrated great potential for the molecular breeding of barley varieties with enhanced straw quality for bioenergy applications.